Does conventional body weight reduction decrease anaerobic capacity of boxers in the competition period? - Durkalec-Michalski, K.; Goscianska, I.; Jeszka, J. (Archives of Budo, 2015)
Background and Study Aim: Body weight reduction (BWR) is a serious problem in combat sports. Athletes frequently reduce their body weight in an inappropriate manner, which may have a negative effect on their exercise capacity and health. In view of the above and taking into consideration the limited number of studies conducted on trained boxers, the aim of this study was the knowledge about effect of conventional body weight reduction, used in this sports discipline, on body composition and anaerobic adaptation in athletes. Material and Methods: The study involved 20 trained male boxers. The energy balance was determined based on the 4-day ongoing recording of food and liquids consumption, as well as 24-h energy expenditure estimated using heart rate monitoring. Body composition was measured using bioelectric impedance. The Wingate test was performed in order to determine the effect of BWR on anaerobic capacity. Results: Boxers reduced their body weight on average by 5.4% within 7.8 ± 3.2 days. The energy value of their diet during BWR was by 51.5% lower (p<0.001) comparing to the training (preparation) period. It was observed that conventional BWR results in the reduction (p<0.05) not only of fat mass (BWRPRE: 11.7 ± 3.6 kg vs. BWRPOST: 10.7 ± 3.9 kg), but to a considerable extent (p<0.01) also fat free mass (BWRPRE: 61.1 ± 9.5 kg vs. BWRPOST: 59.2 ± 9.3 kg) and body water (BWRPRE: 44.8 ± 6.7 l vs. BWRPOST: 43.8 ± 6.4 l). A deterioration was also recorded (p<0.001) in peak power (-9.3%), average power (-4.7%) and time at peak power (+55%), as well as (p<0.001) minimum power (-3.9%). Conclusion: Conventional BWR adopted by boxers, connected with dietary limitations, is rapid and has an adverse effect on body composition and anaerobic capacity. This is seems necessary to implement an adequate education program in this respect, making it possible for athletes and coaches to plan a rational body weight reduction strategy in the pre-competition period.